Pemerintah Sebagai Subjek Hukum Administrasi: Tinjauan Atas Tanggung Jawab Negara Dalam Maladministrasi Publik - Tamaulina Br Sembiring; Defania Azura; Nabila putri manulang; Muhammad hirzi aldivie ginting; Marko Harahap (Journal of Innovative and Creativity, 2025)
In a state of law, the government has an important role as a subject of administrative law that is bound by regulations. Public maladministration, namely actions that deviate from procedures, harms the community and reduces public trust in institutions. This problem arises because of abuse of authority and discrimination in public services, so it is important to assess the responsibility of the state in dealing with maladministration. This study aims to analyze the position of the government as a subject of administrative law and the mechanism of accountability in cases of maladministration. The study includes identifying forms of maladministration, a map of the legal framework on government responsibility, and challenges in demanding state accountability. The method used is qualitative with a literature study, involving a review of literature and current regulations. The results of the study show that although the principle of state responsibility is recognized, its implementation faces serious challenges. These challenges include complex bureaucracy and limited supervisory institutions, so systemic improvements and institutional strengthening are needed for better enforcement of accountability.